Analisis Pengaruh Marketing Mix Terhadap Keputusan Nasabah Memilih BSI Griya Studi Pada Bank BSI KCP Natar - Khomsatul Khoiriyah; Weny Rosilawati; Syamsul Hilal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by the increasing population in Indonesia which will further increase the need for housing in the future. This study aims to analyze the influence of marketing mix on customer decisions to choose BSI Griya at BSI KCP Natar bank. The method used is a quantitative method. Using primary and secondary data. The population of this study were BSI KCP Natar Bank customers who took BSI Griya financing products as many as 86 respondents with calculations using the slovin formula. The data collected were analyzed using multiple linear regression methods assisted by SPSS 25 software. The results showed that all Marketing mix variables (Product, price, location, promotion, employees, physical evidence, and process) had a positive and significant effect with a significance value <0.05. Product has a significance value of 0.00 <0.05, Price significance value of 0.00 <0.05, Location significance value of 0.00 <0.05, Promotion significance value of 0.001 <0.05, Employees significance value of 0.00 <0.05, Physical evidence significance value of 0.00 <0.05, Process significance value of 0.00 <0.05. and the calculated F value of 1034.606> 2.129 with a significance of 0.00 so that the Marketing mix (Product, price, place, promotion, people, physical evidence, and process) simultaneously has a significant positive effect.